Relationship between stressors and job burnout: Moderating role of job well-being - Jie WU; Fengmin CHENG; Ruotong YI; Weiqian YU; Chunyan LIU; Mengyu OU (环境与职业医学)
BackgroundEnhancing the sense of honor and belonging among medical staff is a key component of establishing a modern hospital management system. Compared to medical staff at general hospitals, medical staff at oncology hospitals are more prone to job burnout, yet few studies in China have focused on job burnout among employees in oncology hospitals.ObjectiveTo propose a hypothetical model in which job well-being moderates the relationship between stressors and occupational burnout, to explore how stressors influence burnout and potential moderating role of job well-being, and to provide better understanding of job burnout and motivate employees based on the double-edge sword effect of stressors.MethodsA cross-sectional survey was conducted in May 2022 at a tertiary oncology specialty hospital in Chongqing, China. A total of 1 898 medical staff were recruited. Data were collectedthrough four scales including a general information questionnaire, Maslach Burnout Inventory-Human Service Survey, Work Stressor Scale, and Occupational Well-being Scale for Medical Staff. Independent sample t-tests and one-way ANOVA were used for univariate comparisons of job burnout. Pearson correlation analysis was employed to examine the relationships between job burnout, stressors, and job well-being. Hierarchical linear regression was conducted to identify factors influencing job burnout and to examine potential moderating role of job well-being in the relationship between stressors and job burnout.ResultsA total of 2 123 questionnaires were distributed, with 1 898 valid responses, yielding an effective response rate of 89.4%. The prevalence of job burnout was 60.1%. The correlation coefficient was 0.717 (P<0.001) between stressors and burnout, −0.784 (P<0.05) between job well-being and burnout, and −0.744 (P<0.001) between stressors and job well-being. The quadratic stressors showed a statistically significant effect on burnout (β=0.404, P<0.01). Job well-being positively moderated the relationship between the linear stressors and burnout (β=1.289, P<0.001) and negatively moderated the relationship between the quadratic stressors and job burnout (β=−0.571, P<0.01), explaining 7.1% of the variance.ConclusionJob burnout prevalence is relatively high among employees in oncology hospitals. There is a curvilinear relationship between stressors and job burnout, with job well-being moderating this relationship. From a practical perspective, it is recommended to establish a tiered stress alert system to monitor employees’ stress levels and prevent prolonged exposure to high-pressure conditions. Additionally, improving employees’ job well-being through institutional incentives and developmental support can enhance its moderating role in mitigating the adverse effects of stressors on job burnout. Meanwhile, fostering coordinated responses between organizations and individuals is crucial for strengthening mental health management systems, thereby supporting a healthy, stable, and sustainable development of the healthcare workforce.